Kontrol Diri Memoderasi Pengaruh Fasilitas E-Wallet dan Gaya Hidup Terhadap Perilaku Konsumtif Gen Z - Silvi Alvianingrum; Luh Putu Mahyuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Broad access to the internet, social media, and digital financial services has made e-wallets and paylater increasingly embedded in everyday life. Transaction convenience and aggressive promotions drive consumptive behavior, especially among Gen Z, while previous studies on the influence of e-wallet usage and lifestyle on consumptive behavior have shown inconsistent findings. This study aims to analyze the effect of e-wallet usage and lifestyle on the consumptive behavior of Generation Z, with self-control as a moderating variable. The research method employed is a quantitative approach using surveys and SEM analysis on Gen Z respondents.The findings are expected to provide a comprehensive understanding of the role of digital financial technology and psychological factors in shaping young people’s consumption behavior. Furthermore, this study can serve as input for digital service providers and policymakers to encourage healthier and more sustainable consumption behavior.